2024
DOI: 10.1002/exp.20230078
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive scaffolds for tissue engineering: A review of decellularized extracellular matrix applications and innovations

Juan Liu,
Qingru Song,
Wenzhen Yin
et al.

Abstract: Decellularized extracellular matrix (dECM) offers a three‐dimensional, non‐immunogenic scaffold, enriched with bioactive components, making it a suitable candidate for tissue regeneration. Although dECM‐based scaffolds have been successfully implemented in preclinical and clinical settings within tissue engineering and regenerative medicine, the mechanisms of tissue remodeling and functional restoration are not fully understood. This review critically assesses the state‐of‐the‐art in dECM scaffolds, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 192 publications
0
0
0
Order By: Relevance
“…The fibrous scaffold was designed and aligned to mimic the ordered structure of the extracellular matrix (ECM) , (Figure A). The well-aligned fibrous scaffold is beneficial for guiding cell behavior, improving electrical conductivity, reducing the inflammatory response, and facilitating innervation and vascularization. In addition, they possess good flexibility, high surface area-to-volume ratio, and high porosity compared to other wound dressings, which are favorable for cell attachment, proliferation, and tissue regeneration. The prepared fSPP was displayed, as shown in Figure B. External activation of the piezoelectric scaffolds was achieved using LIPUS, providing acoustic and electrical stimulations for neurogenesis and burn wound healing with minimal thermal effect.…”
Section: Resultsmentioning
confidence: 99%
“…The fibrous scaffold was designed and aligned to mimic the ordered structure of the extracellular matrix (ECM) , (Figure A). The well-aligned fibrous scaffold is beneficial for guiding cell behavior, improving electrical conductivity, reducing the inflammatory response, and facilitating innervation and vascularization. In addition, they possess good flexibility, high surface area-to-volume ratio, and high porosity compared to other wound dressings, which are favorable for cell attachment, proliferation, and tissue regeneration. The prepared fSPP was displayed, as shown in Figure B. External activation of the piezoelectric scaffolds was achieved using LIPUS, providing acoustic and electrical stimulations for neurogenesis and burn wound healing with minimal thermal effect.…”
Section: Resultsmentioning
confidence: 99%
“…Structures with arbitrary geometric shape, mechanical and biological heterogeneity can be manufactured to better promote cell infiltration and tissue regeneration. 3D printing technology is widely used in vitro to reconstruct the structure and function of living tissue, skin and cartilage have been printed and implanted in patients, and even have been used to prepare complex artificial hearts. The technical difficulties of replicating the heterogeneity of urinary organs and the limited selection of biomaterials that encapsulate the complex extracellular matrix components, but a large number of studies have demonstrated the potential of 3D bioprinting to create functional urinary organs in clinical transplantation and in vitro disease models of organs . Bioprinting has shown potential in the field of urological trauma repair.…”
Section: D Bioprintingmentioning
confidence: 99%